Análise do standard probatório da infração antecedente enquanto critério de tipicidade objetiva ao crime de lavagem de dinheiro - Bowen, Vitor Teixeira Rampazzo (2024)
This work aims to analyze the possible standards of proof of the antecedent offense as the criterion for the typicity of the crime of money laundering, specifically for the filing of charges and for conviction. To achieve this, it was necessary to demonstrate the autonomy of the antecedent offense from the crime of money laundering, as well as criticisms of the prominent role of money laundering in criminal prosecution. The legal interests in the crime of money laundering were also analyzed in relation to the autonomy of offenses. Additionally, legal epistemology and the pursuit of truth in criminal proceedings were discussed, along with evidentiary standards. Lastly, the different schools of thought and their respective foundations regarding the advocated standards of proof in each context were delineated